Testament mieszczanki szadkowskiej Doroty Czygańskiej z Lipińskich z 1693 roku - Szkutnik, Piotr (Biuletyn Szadkowski, 2014)
Szadek has a well-preserved set of town records for the period 1401-1697, consisting of 32 volumes. These books contain a number of legal entries, including testaments. The last will of Dorota Czygańska bom Lipińska, written in 1693, found in one of the books, is an interesting document throwing light on many aspects of life in old Poland. The testatrix was a wealthy townswoman possessing a homestead, four plots within the town and much livestock. The property was mainly inherited by her two sons, with a bequest to her brother, Jakub Lipiński, a priest. This suggests that the testatrix belonged to the town's elite. The mother's ambition was that her younger son should receive education. The bequests for the younger child contain conditions conceming his education.